Implementasi Metode Forward Chaining dalam Mengidentifikasi Kepribadian Siswa - Raju Wandira; Jufriadif Naam (Universitas Muhammadiyah Riau, 2020)
Personality is the overall psychological and physical aspects of an individual reacting and interacting with other individuals. Personality is a prominent and often shown thing that exists in an individual. Students have different personalities, and that will affect the quality of learning. To be able to improve the quality of learning, schools need to identify and understand the personality of their students. So that appropriate learning methods can be applied and the selection of appropriate majors in tertiary institutions. To identify student personality can be done with a system called the expert system. The expert system identifies student personalities using the forward chaining method obtained from State High School 1 Candung students (SMAN 1 Candung), Agam Regency. In the forward chaining method, the reasoning process starts from the facts first to test the truth of the hypothesis. The process of finding the data starts from the premises to the final conclusion. Creating an expert system for identifying student personalities using the PHP Programming Language and MySQL Database. The result of testing this method is knowing the personality of students so that appropriate learning methods can be applied, majors recommendations and advice on the type of work according to the personality of the student. Personality expert system has been able to identify the personality of students in determining learning methods and choosing majors as well as suggestions for the type of work. Personality expert systems have been able to identify student personalities in determining learning methods and selection of majors as well as suggestions for types of work. This expert system is already running well and can be recommended to help students, teachers and schools in improving the quality of learning in schools